Pengaruh Harga Dan Produksi Karet Terhadap Pendapatan Petani Karet di Desa Aurcino Kecamatan VII Koto Kabupaten Tebo - Kartika Sari; M Nazori Majid; Muhammad Subhan (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis discusses and aims to find out about the effect of Rubber Price and Production on the Opinion of Rubber Farmers in Aurcino Village, Kec.VII Koto, Tebo Regency. The data of this study are primary data obtained directly from the first source either from individuals or individuals such as the results of filling out questionnaires. This study uses a quantitative approach using a multiple linear regression analysis method assisted by SPSS (Statistical Package For Social Science) software 22. The results of the research conducted showed that (1) the price of rubber had a positive and significant effect on the income of rubber farmers in Aurcino Village, Kec.VII Koto, Tebo Regency. (2) Rubber Production has a Positive and Significant effect on the income of rubber farmers in Aurcino Village, Kec.VII Koto, Tebo Regency. (3) The price and production of rubber have a significant effect on the income of farmers in Aurcino Village, Kec.VII Koto, Tebo Regency.